‘Scrotal “Sack” – A Bag of Worms’: Scrotal Arteriovenous Malformation - Shruti Thakur; Suresh Kumar Thakur; Anupam Jhobta; Charu Smita Thakur (Journal of Human Reproductive Sciences)
Scrotal arteriovenous malformation (AVM) is an unusual entity with its own important clinical implications. Described only as a few case reports in medical literature, it not only can cause life-threatening haemorrhage because of its superficial location in the scrotum but also can result in infertility. We report the case of a 35-year-old man who had a progressively increasing scrotal swelling for almost 20 years and now presented for infertility workup. He had oligospermia on semen analysis with a normal testosterone level and no history of testicular infection or scrotal surgery. On scrotal sonography and computed tomography angiography, he was diagnosed to have bilateral scrotal AVMs which may have resulted in his oligospermia. Pre-operative embolisation and surgery was offered as a treatment option which the patient declined and was lost to follow-up. However, this case describes scrotal AVM as an important and possibly correctable cause of infertility. Usually diagnosed as scrotal lymphedema clinically, the case has been reported so that the clinician should be aware of this entity as a plausible cause of male infertility and the treatment could be refined and accelerated.